(untitled) (International Journal of Food and Nutritional Sciences, 2025)
This research focused on the formulation and evaluation of functional pasta developed using soya flour and whole wheat flour. The primary aim was to enhance protein and dietary fiber content while maintaining acceptable sensory attributes. Three pasta samples (S1, S2, S3) were developed by progressively replacing whole wheat flour with soya okhara at 10%, 20%, and 30%. The samples were evaluated for proximate composition and sensory properties. Sensory evaluation revealed that Sample 2, formulated with 30% soya okara, was well accepted by the panel members, showing favorable scores for appearance (8.2), color (8.4), texture (8.1), and taste (8.3) and mouthfeel (8.4). The study demonstrates that incorporating soya okara in pasta significantly improves nutritional and functional properties while maintaining consumer appeal at moderate substitution levels.